PERAN PEREMPUAN DALAM PENCEGAHAN STUNTING DI KECAMATAN BUNAKEN KOTA MANADO PROVINSI SULAWESI UTARA - Timban, Jean Fanny Junita; Tangkere, Ellen Grace; Lumingkewas, Jelly Ribka Danaly (Universitas Sam Ratulangi, 2020)
Stunting in under-five children is a reduced growth rate primarily caused by chronic undernutrition that leads to a child having height much less than is normal for age. This condition manifests mostly after two years old. The definition of stunting according to the World Health Organization (WHO) is for the